2013
DOI: 10.1002/2013eo190005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sea Surface Temperature for Cyclone Intensity Prediction Needs a Relook

Abstract: If a cyclone's track and intensity can be predicted precisely, the losses due to cyclones can be minimized. While efforts are under way to improve the understanding of the physics of the problem of track and intensity prediction, it is worthwhile to look again at the efficiency of the input parameters presently used in models and to look for new approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Intense upper ocean mixing events caused by the strong hurricane winds can quickly erode the thermal signature of subsurface warm or cold features (Pickard and Emery, 1990), leading to SST misrepresenting the ocean thermal energy, and potential TC intensity. Several studies (e.g., Mao et al, 2000;Shay et al, 2000;Ali et al, 2007Ali et al, , 2013Mainelli et al, 2008;Lin et al, 2013b) demonstrated the importance of ocean thermal energy, represented by warm ocean features.…”
Section: Tropical Cyclonesmentioning
confidence: 99%
“…Intense upper ocean mixing events caused by the strong hurricane winds can quickly erode the thermal signature of subsurface warm or cold features (Pickard and Emery, 1990), leading to SST misrepresenting the ocean thermal energy, and potential TC intensity. Several studies (e.g., Mao et al, 2000;Shay et al, 2000;Ali et al, 2007Ali et al, , 2013Mainelli et al, 2008;Lin et al, 2013b) demonstrated the importance of ocean thermal energy, represented by warm ocean features.…”
Section: Tropical Cyclonesmentioning
confidence: 99%
“…Therefore, cooling of SST due to strong cyclonic winds of the same day is ruled out. Since the number of cyclone with a negative correlation between CI and SST are more than those having positive correlations, Ali et al [17] suggested to have a relook at the use of satellite derived SST as a measure of CI.…”
Section: Ssha Sst and CImentioning
confidence: 99%
“…MLP approach has been used by Ali et al . (, , , , ) to estimate the tropical cyclone heat potential and the ocean windstress. We tried all the models and found that an MLP network provided the least error and best results.…”
Section: Approachmentioning
confidence: 99%
“…( , 2012cAli et al . ( , 2013aAli et al . ( , 2013b to estimate the tropical cyclone heat potential and the ocean windstress.…”
Section: Ann Approachmentioning
confidence: 99%